Analgesic effect of intranasal ketamine in the treatment of chronic cancer pain - Secundino González Pardo; Lourdes González-Longoria Boada; Francisco López Muñoz (Medisur)
Background: cancer pain remains difficult to treat, especially when the patient is resistant to opioids. More and more alternatives are being sought to counteract and improve the symptoms caused by the disease. One of them is ketamine, which acts as an antagonist of NMDA receptors that are associated in response to pain. Objective: to evaluate the efficacy of the analgesic response to cancer pain with the intranasal administration of ketamine as an adjuvant in pharmacological treatment. Methods: research carried out in Ecuador pain clinic. A randomized, double-blind, placebo-controlled cohort study was conducted. 142 participants were included. Two treatments were administered: intranasal ketamine and placebo, which were used in combination with morphine. Participants received periodic visual analog pain scale assessments for three consecutive days. Results: the mean age was 69.11 ± 9.77 years. The pancreatic head tumor (44.37%) was the most frequently carcinoma. There were significant differences between administered treatments, clinical aspects and pain (p < 0.05). The patients who were treated with ketamine had a more relevant analgesic effect than the patients who received the placebo. The main side effect was nausea (11.43%). Conclusions: patients treated with ketamine experienced better analgesia than the control group. Ketamine represents an option for pain in those who do not respond to conventional opioid treatment. Adverse effects may limit its application in some patients.